Method for prolonging fatigue life of material based on laser shock peening technology
By adopting two laser impact enhancement methods in laser impact enhancement technology and using different absorption layers and constraint layers, the problems of excessive thermal damage and deformation during laser impact enhancement are solved, and a significant improvement in the fatigue life of the material is achieved.
Patent Information
- Application Number
- CN202411925641.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When using laser impact enhancement technology to modify the surface of the material to improve the fatigue life of the material, there are problems of excessive thermal damage and deformation, which affects the improvement of the fatigue life of the material.
The method of two laser impact strengthening is adopted, and different absorption layers and constraint layers are used during the two laser impact strengthening. The specific steps include spraying the absorption layer and constraint layers to the surface of the material to be strengthened in sequence, performing the first laser impact strengthening, spraying again and performing the second laser impact strengthening.
It effectively avoids excessive thermal damage and deformation during laser impact strengthening, and significantly improves the fatigue life of the material.
Smart Images

Figure BDA0005209187570000051 
Figure BDA0005209187570000052 
Figure BDA0005209187570000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser shock peening surface modification, and in particular to a method for improving material fatigue life based on laser shock peening technology. Background Art
[0002] Fatigue refers to the phenomenon that the material performance gradually declines due to the existence of internal microscopic defects when the material is subjected to alternating loads, while fatigue life refers to the number of cyclic loads that the material can withstand under a given load amplitude. The length of fatigue life directly affects the reliability and service life of the material. Therefore, how to improve the fatigue life of the material has become a research hotspot for technicians in this field. Existing studies have found that appropriate surface treatment of the material surface can effectively eliminate or repair microscopic defects on the material surface, thereby effectively improving the fatigue life of the material.
[0003] Laser shock peening technology is an emerging surface treatment technology that uses the plasma shock mechanics effect induced by a high-power density, low-pulse width laser beam to modify the material surface. Compared with traditional surface treatment technologies such as hardening and quenching, laser shock peening technology has almost no thermal effect on the material surface and has significant advantages such as cleanliness, environmental protection, high operating efficiency and strong controllability.
[0004] However, with the practical application of laser strengthening technology, when using laser strengthening technology to modify the material surface to improve the fatigue life of the material, a large amount of energy is required to generate the laser beam, and the energy of the laser beam has a certain spatial non-uniformity, which will cause excessive thermal damage and deformation on the material surface, which is not conducive to improving the fatigue life of the material.
[0005] Therefore, improving the laser strengthening technology and developing a laser strengthening technology solution that can effectively avoid excessive thermal damage and deformation while effectively improving the fatigue life of the material has become a technical problem that needs to be urgently solved by technical personnel in this field. Summary of the invention
[0006] The purpose of the present invention is to provide a method for improving the fatigue life of materials based on laser shock peening technology. The method for improving the fatigue life of materials based on laser shock peening technology can effectively avoid excessive thermal damage and deformation, and at the same time can effectively improve the fatigue life of materials.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for improving material fatigue life based on laser shock peening technology, comprising the following steps:
[0009] 1) The absorption layer A and the constraint layer A are uniformly sprayed on the surface of the material to be strengthened in sequence, and then the surface of the material to be strengthened is subjected to laser shock strengthening once;
[0010] 2) After the first laser shock peening in step 1 is completed, the absorption layer B and the constraint layer B are sprayed uniformly on the surface of the material to be strengthened in sequence, and then the surface of the material to be strengthened is subjected to a second laser shock peening.
[0011] Furthermore, in step 1), the absorption layer A is silicon carbide or aluminum oxide.
[0012] Furthermore, in step 1), the absorption layer A has a thickness of 0.05 μm to 0.20 μm.
[0013] Furthermore, in step 1), the constrained layer A is water or K9 glass.
[0014] Furthermore, in step 1), the thickness of the constraint layer A is 3 mm to 5 mm.
[0015] Furthermore, in step 1), the parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap.
[0016] Furthermore, in step 2), before the absorption layer B and the constraint layer B are uniformly sprayed sequentially onto the surface of the material to be strengthened, the residual constraint layer A on the surface of the material to be strengthened needs to be removed.
[0017] Furthermore, in step 2), the absorption layer B is ferroferric oxide or graphite.
[0018] Furthermore, in step 2), the absorption layer B has a thickness of 50 μm to 90 μm.
[0019] Furthermore, in step 2), the constrained layer B is K9 glass.
[0020] Furthermore, in step 2), the thickness of the constraint layer B is 3 mm to 5 mm.
[0021] Furthermore, in step 2), the parameters of the secondary laser shock peening are: laser wavelength 1064nm, pulse width 6ns, laser energy density 12.7GW / cm 2 , spot diameter 1mm, spot 50% overlap.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention provides a method for improving the fatigue life of materials based on laser shock peening technology. Through two laser shock peening processes, different absorption layers and constraint layers are selected during the two laser shock peening processes, thereby effectively avoiding excessive thermal damage and deformation during the shock peening process and effectively improving the fatigue life of the material. DETAILED DESCRIPTION
[0024] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0025] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0026] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0029] In the following embodiment, a method for improving the fatigue life of a material based on laser shock peening technology comprises the following steps:
[0030] 1) The absorption layer A and the constraint layer A are uniformly sprayed on the surface of the material to be strengthened in sequence, and then the surface of the material to be strengthened is subjected to laser shock strengthening once;
[0031] Wherein, the absorption layer A is silicon carbide or aluminum oxide;
[0032] Wherein, the thickness of the absorption layer A is 0.05 μm to 0.20 μm;
[0033] Wherein, the constraining layer A is water or K9 glass;
[0034] Wherein, the thickness of the constraint layer A is 3 mm to 5 mm;
[0035] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap;
[0036] 2) After the first laser shock peening in step 1) is completed, the absorption layer B and the constraint layer B are uniformly sprayed on the surface of the material to be strengthened in sequence, and then the surface of the material to be strengthened is subjected to a second laser shock peening;
[0037] Before the absorption layer B and the constraint layer B are uniformly sprayed on the surface of the material to be strengthened, the residual constraint layer A on the surface of the material to be strengthened needs to be removed;
[0038] Wherein, the absorption layer B is ferroferric oxide or graphite;
[0039] Wherein, the thickness of the absorption layer B is 50 μm to 90 μm;
[0040] Wherein, the constrained layer B is K9 glass;
[0041] Wherein, the thickness of the constraint layer B is 3 mm to 5 mm;
[0042] The parameters of the secondary laser shock peening are: laser wavelength 1064nm, pulse width 6ns, laser energy density 12.7GW / cm 2 , spot diameter 1mm, spot 50% overlap.
[0043] In the following embodiments, titanium alloy TC4 is used as an example for laser shock strengthening. Those skilled in the art can refer to the method described in the present invention to perform laser shock strengthening on any material to be strengthened.
[0044] Embodiments 1 to 4
[0045] A method for improving material fatigue life based on laser shock peening technology
[0046] 1) Silicon carbide (absorption layer A) and water with a thickness of 3 mm (constraint layer A) are uniformly sprayed on the surface of titanium alloy TC4 in sequence, and then the surface of titanium alloy TC4 is subjected to laser shock strengthening once;
[0047] Wherein, the thickness of the absorption layer A is shown in Table 1;
[0048] Table 1 Thickness of the absorption layer A
[0049]
[0050]
[0051] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap;
[0052] 2) After the first laser shock strengthening in step 1) is completed, the residual constraint layer A on the surface of the material to be strengthened is removed, and then ferrosoferric oxide (absorption layer B) with a thickness of 50 μm and K9 glass (constraint layer B) with a thickness of 3 mm are evenly sprayed on the surface of the titanium alloy TC4 in sequence, and finally the surface of the titanium alloy TC4 is subjected to secondary laser shock strengthening;
[0053] The parameters of the secondary laser shock peening are: laser wavelength 1064nm, pulse width 6ns, laser energy density 12.7GW / cm 2 , spot diameter 1mm, spot 50% overlap.
[0054] The fatigue life test was performed on the titanium alloy TC4 after laser shock strengthening in Examples 1 to 4, and the fatigue life test results are shown in Table 2;
[0055] Table 2 Fatigue life test results
[0056]
[0057] It can be seen from the data in Table 2 that the thickness of the absorption layer A will affect the fatigue life of the titanium alloy TC4. In the test range of 0.05μm to 0.20μm, the fatigue life of the titanium alloy TC4 shows a trend of first increasing and then decreasing, and the optimal fatigue life is reached at 0.10μm, so the thickness of the absorption layer A is preferably 0.10μm.
[0058] Embodiments 5 to 8
[0059] A method for improving material fatigue life based on laser shock peening technology
[0060] 1) Silicon carbide (absorption layer A) and water (constraint layer A) with a thickness of 0.10 μm are uniformly sprayed on the surface of titanium alloy TC4 in sequence, and then the surface of titanium alloy TC4 is subjected to laser shock strengthening once;
[0061] Wherein, the thickness of the constrained layer A is shown in Table 3;
[0062] Table 3 Thickness of constraint layer A
[0063]
[0064] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap;
[0065] 2) After the first laser shock strengthening in step 1) is completed, the residual constraint layer A on the surface of the material to be strengthened is removed, and then ferrosoferric oxide (absorption layer B) with a thickness of 50 μm and K9 glass (constraint layer B) with a thickness of 3 mm are evenly sprayed on the surface of the titanium alloy TC4 in sequence, and finally the surface of the titanium alloy TC4 is subjected to secondary laser shock strengthening;
[0066] The parameters of the secondary laser shock peening are: laser wavelength 1064nm, pulse width 6ns, laser energy density 12.7GW / cm 2 , spot diameter 1mm, spot 50% overlap.
[0067] The fatigue life test was performed on the titanium alloy TC4 after laser shock strengthening in Examples 5 to 8. The fatigue life test results are shown in Table 4.
[0068] Table 4 Fatigue life test results
[0069]
[0070] It can be seen from the data in Table 4 that the thickness of the constraint layer A will affect the fatigue life of the titanium alloy TC4. Within the test range of 3 mm to 5 mm, the fatigue life of the titanium alloy TC4 shows a trend of first increasing and then decreasing, and reaches the optimal fatigue life at 4.5 mm. Therefore, the thickness of the constraint layer A is preferably 4.5 mm.
[0071] Examples 9 to 12
[0072] A method for improving material fatigue life based on laser shock peening technology
[0073] 1) Silicon carbide (absorption layer A) with a thickness of 0.10 μm and water (constraint layer A) with a thickness of 4.5 mm are uniformly sprayed on the surface of titanium alloy TC4 in sequence, and then the surface of titanium alloy TC4 is subjected to laser shock strengthening once;
[0074] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap;
[0075] 2) After the first laser shock strengthening in step 1) is completed, the residual constraint layer A on the surface of the material to be strengthened is removed, and then ferroferric oxide (absorption layer B) and K9 glass with a thickness of 3 mm (constraint layer B) are uniformly sprayed on the surface of the titanium alloy TC4 in sequence, and finally the surface of the titanium alloy TC4 is subjected to secondary laser shock strengthening;
[0076] Wherein, the thickness of the absorption layer B is shown in Table 5;
[0077] Table 5 Thickness of the absorption layer B
[0078]
[0079] The parameters of the secondary laser shock peening are: laser wavelength 1064nm, pulse width 6ns, laser energy density 12.7GW / cm 2 , spot diameter 1mm, spot 50% overlap.
[0080] The fatigue life test was performed on the titanium alloy TC4 after laser shock strengthening in Examples 9 to 12. The fatigue life test results are shown in Table 6.
[0081] Table 6 Fatigue life test results
[0082]
[0083] It can be seen from the data in Table 6 that the thickness of the absorption layer B will affect the fatigue life of the titanium alloy TC4. In the test range of 50μm to 90μm, the fatigue life of the titanium alloy TC4 shows a trend of first being constant and then decreasing. Combined with economic needs, the thickness of the absorption layer B is preferably 50μm.
[0084] Embodiments 13 to 16
[0085] A method for improving material fatigue life based on laser shock peening technology
[0086] 1) Silicon carbide (absorption layer A) with a thickness of 0.10 μm and water (constraint layer A) with a thickness of 4.5 mm are uniformly sprayed on the surface of titanium alloy TC4 in sequence, and then the surface of titanium alloy TC4 is subjected to laser shock strengthening once;
[0087] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap;
[0088] 2) After the first laser shock strengthening in step 1) is completed, the residual constraint layer A on the surface of the material to be strengthened is removed, and then ferrosoferric oxide (absorption layer B) and K9 glass (constraint layer B) with a thickness of 50 μm are evenly sprayed on the surface of the titanium alloy TC4 in sequence, and finally the surface of the titanium alloy TC4 is subjected to secondary laser shock strengthening;
[0089] Wherein, the thickness of the constrained layer B is shown in Table 7;
[0090] Table 7 Thickness of the absorption layer B
[0091]
[0092] The parameters of the secondary laser shock peening are: laser wavelength 1064nm, pulse width 6ns, laser energy density 12.7GW / cm 2 , spot diameter 1mm, spot 50% overlap.
[0093] The fatigue life test was performed on the titanium alloy TC4 after laser shock strengthening in Examples 13 to 16. The fatigue life test results are shown in Table 8.
[0094] Table 8 Fatigue life test results
[0095]
[0096] It can be seen from the data in Table 8 that the thickness of the constraint layer B will affect the fatigue life of the titanium alloy TC4. Within the test range of 3mm to 5mm, the fatigue life of the titanium alloy TC4 shows a trend of first increasing and then decreasing, and reaches the optimal fatigue life at 4mm, so the thickness of the constraint layer B is preferably 4mm.
[0097] Embodiment 17
[0098] A method for improving material fatigue life based on laser shock peening technology
[0099] 1) Aluminum oxide (absorption layer A) with a thickness of 0.10 μm and water (constraint layer A) with a thickness of 4.5 mm are uniformly sprayed on the surface of titanium alloy TC4 in sequence, and then the surface of titanium alloy TC4 is subjected to laser shock strengthening once;
[0100] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap;
[0101] 2) After the first laser shock strengthening in step 1) is completed, the residual constraint layer A on the surface of the material to be strengthened is removed, and then ferroferric oxide (absorption layer B) with a thickness of 50 μm and K9 glass (constraint layer B) with a thickness of 4 mm are evenly sprayed on the surface of the titanium alloy TC4 in sequence, and finally the surface of the titanium alloy TC4 is subjected to secondary laser shock strengthening;
[0102] The parameters of the secondary laser shock peening are: laser wavelength 1064nm, pulse width 6ns, laser energy density 12.7GW / cm 2 , spot diameter 1mm, spot 50% overlap.
[0103] The fatigue life test was performed on the titanium alloy TC4 after laser shock strengthening in Example 17. The test showed that the number of cycles of the titanium alloy TC4 after laser shock strengthening in Example 17 at 600° C. was 960 times.
[0104] Embodiment 18
[0105] A method for improving material fatigue life based on laser shock peening technology
[0106] 1) Silicon carbide (absorption layer A) with a thickness of 0.10 μm and K9 glass (constraint layer A) with a thickness of 4.5 mm are uniformly sprayed on the surface of titanium alloy TC4 in sequence, and then the surface of titanium alloy TC4 is subjected to laser shock strengthening once;
[0107] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap;
[0108] 2) After the first laser shock strengthening in step 1) is completed, the residual constraint layer A on the surface of the material to be strengthened is removed, and then ferroferric oxide (absorption layer B) with a thickness of 50 μm and K9 glass (constraint layer B) with a thickness of 4 mm are evenly sprayed on the surface of the titanium alloy TC4 in sequence, and finally the surface of the titanium alloy TC4 is subjected to secondary laser shock strengthening;
[0109] The parameters of the secondary laser shock peening are: laser wavelength 1064nm, pulse width 6ns, laser energy density 12.7GW / cm 2 , spot diameter 1mm, spot 50% overlap.
[0110] The fatigue life test was performed on the titanium alloy TC4 after laser shock strengthening in Example 18. The test showed that the number of cycles of the titanium alloy TC4 after laser shock strengthening in Example 18 at 600° C. was 980 times.
[0111] Embodiment 19
[0112] A method for improving material fatigue life based on laser shock peening technology
[0113] 1) Silicon carbide (absorption layer A) with a thickness of 0.10 μm and water (constraint layer A) with a thickness of 4.5 mm are uniformly sprayed on the surface of titanium alloy TC4 in sequence, and then the surface of titanium alloy TC4 is subjected to laser shock strengthening once;
[0114] The parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm 2 , spot diameter 5mm, spot 50% overlap;
[0115] 2) After the first laser shock strengthening in step 1) is completed, the residual constraint layer A on the surface of the material to be strengthened is removed, and then a graphite with a thickness of 50 μm (absorption layer B) and a K9 glass with a thickness of 4 mm (constraint layer B) are uniformly sprayed on the surface of the titanium alloy TC4 in sequence, and finally the surface of the titanium alloy TC4 is subjected to a second laser shock strengthening;
[0116] The parameters of the secondary laser shock peening are: laser wavelength 1064nm, pulse width 6ns, laser energy density 12.7GW / cm 2 , spot diameter 1mm, spot 50% overlap.
[0117] The fatigue life test was performed on the titanium alloy TC4 after laser shock strengthening in Example 19. The test showed that the number of cycles of the titanium alloy TC4 after laser shock strengthening in Example 19 at 600° C. was 940 times.
[0118] In addition, the present invention also uses β-type titanium alloy, austenitic stainless steel and other materials as materials to be strengthened for laser shock strengthening. It has been verified that no matter what kind of material is used, using 0.10μm thick silicon carbide as the absorption layer A, 4.5mm thick water as the constraint layer A, 50μm ferrosoferric oxide as the absorption layer, and 4mm thick K9 glass as the constraint layer B can most effectively improve the fatigue life of the material.
[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for improving material fatigue life based on laser shock peening technology, characterized in that: The following steps are involved: 1) The absorption layer A and the constraint layer A are uniformly sprayed on the surface of the material to be strengthened in sequence, and then the surface of the material to be strengthened is subjected to laser shock strengthening once; 2) After the first laser shock peening in step 1 is completed, the absorption layer B and the constraint layer B are sprayed uniformly on the surface of the material to be strengthened in sequence, and then the surface of the material to be strengthened is subjected to a second laser shock peening.
2. The method for improving material fatigue life based on laser shock peening technology according to claim 1, characterized in that: In step 1), the absorption layer A is silicon carbide or aluminum oxide; the thickness of the absorption layer A is 0.05 μm to 0.20 μm.
3. The method for improving material fatigue life based on laser shock peening technology according to claim 1, characterized in that: In step 1), the constraint layer A is water or K9 glass; the thickness of the constraint layer A is 3 mm to 5 mm.
4. The method for improving material fatigue life based on laser shock peening technology according to claim 1, characterized in that: In step 1), the parameters of the laser shock peening are: laser wavelength 1053nm, pulse width 15ns, laser energy density 11.9GW / cm2, spot diameter 5mm, and spot 50% overlap.
5. The method for improving material fatigue life based on laser shock peening technology according to claim 1, characterized in that: In step 2), before the absorption layer B and the constraint layer B are uniformly sprayed on the surface of the material to be strengthened in sequence, the residual constraint layer A on the surface of the material to be strengthened needs to be removed.
6. The method for improving material fatigue life based on laser shock peening technology according to claim 1, characterized in that: In step 2), the absorption layer B is ferroferric oxide or graphite; the thickness of the absorption layer B is 50 μm to 90 μm.
7. The method for improving material fatigue life based on laser shock peening technology according to claim 1, characterized in that: In step 2), the constraint layer B is K9 glass; the thickness of the constraint layer B is 3 mm to 5 mm.
8. The method for improving material fatigue life based on laser shock peening technology according to claim 1, characterized in that: In step 2), the parameters of the secondary laser shock peening are: laser wavelength 1064nm, pulse width 6ns, laser energy density 12.7GW / cm2, spot diameter 1mm, and spot 50% overlap.